Low Diversity in Nasal Microbiome Associated With Staphylococcus aureus Colonization and Bloodstream Infections in Hospitalized Neonates. (18th September 2021) - Zhao, Ni; Khamash, Dina F; Koh, Hyunwook; Voskertchian, Annie; Egbert, Emily; Mongodin, Emmanuel F; White, James R; Hittle, Lauren; Colantuoni, Elizabeth; Milstone, Aaron M
Abstract: Background: Staphylococcus aureus is a leading cause of infectious morbidity and mortality in neonates. Few data exist on the association of the nasal microbiome and susceptibility to neonatal S. aureus colonization and infection. Methods: We performed 2 matched case–control studies (colonization cohort—neonates who did and did not acquire S. aureus colonization; bacteremia cohort—neonates who did [colonized neonates] and did not [controls] acquire S. aureus colonization and neonates with S. aureus bacteremia [bacteremic neonantes]). Neonates in 2 intensive care units were enrolled and matched on week of life at time of colonization or infection. Nasal samples were collected weekly until discharge and cultured for S. aureus, and the nasal microbiome was characterized using 16S rRNA gene sequencing. Results: In the colonization cohort, 43 S. aureus –colonized neonates were matched to 82 controls. At 1 week of life, neonates who acquired S. aureus colonization had lower alpha diversity (Wilcoxon rank-sum test P < .05) and differed in beta diversity (omnibus MiRKAT P = .002) even after adjusting for birth weight ( P = .01). The bacteremia cohort included 10 neonates, of whom 80% developed bacteremia within 4 weeks of birth and 70% had positive S. aureus cultures within a few days of bacteremia. Neonates with bacteremia had an increased relative abundance of S. aureus sequences and lower alpha diversity measures compared with colonized neonates and controls. Conclusions: The association of increased S. aureus abundance and decrease of microbiome diversity suggest the need for interventions targeting the nasal microbiome to prevent S. aureus disease in vulnerable neonates.